Last mile delivery in Ecommerce - Karanwal, Juvi (2025)
E-commerce has evolved into not just a rapidly expanding field for research but also an essential component of the tactics that a nation use to compete with other nations. Over the course of the last twenty years, there have been significant advancements in the field of information and communications technology (ICT), as well as a revolution in business methods that were previously unimaginable. In this context, "e-tailing" refers to business-to-consumer (B2C) and business-to-business (B2B) transactions, as well as intranets and extranets, online advertising, electronic banking, online stock trading, online education and consultation services, or simply an online presence of any kind that is utilised for some kind of communication and transaction. E-commerce platforms, which are characterised by asynchronous communication between businesses and potential customers, offer a facility that allows for access at any time and from any location. This facility enables a significant amount of flexibility in the process of conducting transactions with a higher level of involvement. The greatest economies in the world, with a particular emphasis on Binkit, which is India's largest and most convenient hyper-local delivery firm. Blinkit, which was founded in 2013 and was formerly known as Grofers, has made it its aim to ensure that all people living in India have access to products of superior quality at costs that are within their financial means. What differentiates Blinkit from its competitors is the company's capacity to revolutionise India's large and disorganised grocery industry by utilising cutting-edge technology and a delivery strategy that takes only ten minutes. The attainment of the sustainable development objectives is more difficult for third nations because of a lack of resources and understanding on the part of the population. This is something that should be mentioned.